Heromice #1: MIce to the rescue! - Stilton, Geronimo (Geronimo Stilton Heromice, 2015)
Now that the terrible Tony Sludge has escaped from prison, it's to Geronimo Superstilton and the Heromice to defend Muskrat City from the notorious Sewer Rats and to stop an enormouse blackout! Will out heroes be able to defeat their enemies without risking their fur?